COVID-19's impact on the hospitality workforce – new crisis or amplification of the norm?. Issue 9 (29th July 2020) - Baum, Tom; Mooney, Shelagh K.K.; Robinson, Richard N.S.; Solnet, David
Abstract : Purpose: The purpose of this paper is to highlight the immediate impacts of the COVID-19 pandemic on the hospitality workforce in situ between mid-April and June 2020. Design/methodology/approach: This is a viewpoint paper that brings together a variety of sources and intelligence relating the impacts on hospitality work of the COVID-19 pandemic at three levels: macro (global, policy, government), meso (organisational) and micro (employee). It questions whether the situations faced by hospitality workers as a result of the pandemic are seed-change different from the precarious lives they normally lead or just a (loud) amplification of the "normal". Findings: In light of the fluid environment relating to COVID-19, conclusions are tentative and question whether hospitality stakeholders, particularly consumers, governments and the industry itself, will emerge from the pandemic with changed attitudes to hospitality work and hospitality workers. Practical implications: This raises questions about hospitality work for key stakeholders to address in the future, some of which are systemic in terms of how precarious labour forces, critical to the global economy are to be considered by policy makers, organisations in a re-emerging competitive market for talent and for those who chose (or not) to work in hospitality. Social implications: This paper contributes to ongoing debates about precarious work and the extent to which such practices are institutionalised and adopts an "amplification model" that may have value in futures-orientated analysis about hospitality and tourism. Originality/value: This paper is wholly original and a reflection on the COVID-19 crisis. It provides a point of wider reference with regard to responses to crises and their impact on employment in hospitality, highlighting how ongoing change, fluidity and uncertainty serve to magnify and exacerbate the precarious nature of work in the industry.